2004
DOI: 10.1111/j.1432-1033.2004.03987.x
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the activation mechanism of Bordetella pertussis adenylate cyclase by calmodulin using fluorescence spectroscopy

Abstract: The interaction of the adenylate cyclase catalytic domain (AC) of the Bordetella pertussis major exotoxin with its activator calmodulin (CaM) was studied by time-resolved fluorescence spectroscopy using three fluorescent groups located in different regions of AC: tryptophan residues (W69 and W242), a nucleotide analogue (3¢-anthraniloyl-2¢-deoxyadenosine 5¢-triphosphate, Ant-dATP) and a cysteinespecific probe (acrylodan). CaM binding elicited large changes in the dynamics of W242, which dominates the fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
(91 reference statements)
3
11
0
Order By: Relevance
“…No electron density can be found between A225 and L233 of CyaA-ACD, which is the trypsin-sensitive site that divides CyaA-ACD into the N-terminal T25 (25 kDa tryptic fragment) and the Cterminal T18 (Ladant, 1988). Consistent with the fluorescence anisotropy decay data, the C-CaM-bound CyaA-ACD has an elongated shape ( Figure 1) (Gallay et al, 2004). C-CaM adopts the calcium-loaded, open conformation.…”
Section: Introductionsupporting
confidence: 82%
“…No electron density can be found between A225 and L233 of CyaA-ACD, which is the trypsin-sensitive site that divides CyaA-ACD into the N-terminal T25 (25 kDa tryptic fragment) and the Cterminal T18 (Ladant, 1988). Consistent with the fluorescence anisotropy decay data, the C-CaM-bound CyaA-ACD has an elongated shape ( Figure 1) (Gallay et al, 2004). C-CaM adopts the calcium-loaded, open conformation.…”
Section: Introductionsupporting
confidence: 82%
“…It is believed that calmodulin is able to activate ACT by binding to the toxin with a high affinity (0.2 nM), causing a conformational change in a flexible loop between the ATPand CaM-binding subdomains and bringing together the amino acids necessary for ACT to bind and catalyze ATP into cAMP (23,26). In an attempt to corroborate our Blue-Sepharose competition results, we compared the calmodulin activation between ACT from both Bordetella species.…”
Section: Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 77%
“…Extensive biophysical analyses on CyaA activation, however, provided the following information 6 : (i) the CaM bound and unbound AC conformations show a very similar secondary structure content, (ii) the unbound conformation displays a more globular shape than the bound state, with hydrodynamic parameters similar to that of a sphere, (iii) the transition to a more globular shape might be caused by a docking of the α helix H against the CA domain, with an angular displacement of the helix axis that could reach 90°. Conversely, a study of the fluorescence of Trp‐242, located in the helix H, has revealed in the isolated AC a large internal mobility of this residue, which seems to indicate that the isolated AC undergoes a conformational equilibrium between several protein conformations.…”
Section: Introductionmentioning
confidence: 98%